Pemuliaan Padi Gogo Adaptif pada Lahan Kering - Aris Hairmansis; Yullianida Yullianida; Supartopo Supartopo; Suwarno Suwarno (Iptek Tanaman Pangan, 2016)
Upland area in Indonesia has a great potential for rice production. However, only a small portion of the potential upland area has been utilized for rice cultivation with very low productivity. The availability of new technologies in rice management is very important to increase rice production in this marginal area. Improved rice variety is among the most important technologies which has to be introduced to the farmers in upland areas. Upland rice breeding program aims to develop improved rice varieties which are tolerant to diverse abiotic stresses including soil acidity, nutrient deficiency, aluminium toxicity, drought, low light intensity and low temperature. Another important trait in upland rice breeding program is the resistance to blast disease which is the most devastating disease in humid upland area. The increase in genetic diversity of improved rice varieties to blast disease is the key to control the disease. A significant number of improved upland rice varieties have been developed through the breeding program in Indonesian Agency for Agricultural Research and Development. The future challenge in the development of upland rice is the delivery of the high-quality seeds of improved rice varieties to the farmers due to the lack of support from formal seed system in upland areas. Until now upland rice areas are still dominated by traditional varieties and modern varieties which are not developed for upland area but their seeds available in market. Community Based Seed System has been initiated to be implemented in upland area to overcome the problem. Through a strong support from breeding program and proper seed system it is expected the potency of upland rice in Indonesia could be maximized to support the sustainability of rice production in the country.